Andean Berry (Vaccinium meridionale Swartz) Juice improves plasma antioxidant capacity and IL-6 levels in healthy people with dietary risk factors for colorectal cancer (2018)
ABSTRACT: BACKGROUND: Vaccinium meridionale is an Andean Berry that contains bioactive compounds with antioxidant and antiinflammatory properties that can prevent oxidative and pro-inflammatory events associated with colorectal carcinogenesis initiation. OBJECTIVE:Determine if Andean Berry Juice (ABJ) can improve plasma antioxidant capacity and reduce pro-inflammatory cytokines of healthy people with dietary factors for colorectal cancer. METHODS: Nineteen healthy volunteers received 250 mL of ABJ for 14 days. Plasma was obtained before and after the intervention period to analyze antioxidant status through ABTS and isoprostane methods, IL-1, TNF-, IL-6 cytokines and total phenolic content were also analyzed by colorimetric methods. RESULTS: Plasma antioxidant capacity increased (0.222 to 0.555 mM Trolox, p ≤ 0.0001) and isoprostane levels were significantly reduced (264 pg/mL to 197 pg/mL) and positively correlated with the total antioxidant capacity (r = 0.037) after juice consumption, whereas total phenol content decreased (7.08 to 7.04 mg gallic acid equivalent/L, p ≤ 0.0249) at the end of intervention. Plasma IL-6 levels were significantly reduced (p = 0.0230), while IL-1 and TNF did not show changes after juice intake. CONCLUSIONS: These results indicate that ABJ daily intake improves plasma antioxidant capacity and reduces levels of the pro-inflammatory cytokine IL-6 associated with colorectal carcinogenesis